2015
DOI: 10.1038/srep15075
|View full text |Cite
|
Sign up to set email alerts
|

Enduring deficits in memory and neuronal pathology after blast-induced traumatic brain injury

Abstract: Few preclinical studies have assessed the long-term neuropathology and behavioral deficits after sustaining blast-induced neurotrauma (BINT). Previous studies have shown extensive astrogliosis and cell death at acute stages (<7 days) but the temporal response at a chronic stage has yet to be ascertained. Here, we used behavioral assays, immmunohistochemistry and neurochemistry in limbic areas such as the amygdala (Amy), Hippocampus (Hipp), nucleus accumbens (Nac), and prefrontal cortex (PFC), to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 47 publications
(131 reference statements)
5
56
4
Order By: Relevance
“…We were somewhat surprised that the impairment in spatial object recognition did not worsen with increasing blast severity, though, and additional studies to explore how this impairment is affected by the direction and complexity of the blast wave is warranted. These additional studies may also resolve past work that shows blast exposure can differentially affect hippocampal-dependent behaviors (Budde et al, 2013; Sajja et al, 2015; Tompkins et al, 2013; Tweedie et al, 2013), a discrepancy that can be explained by characteristics of the blast loading.…”
Section: Discussionmentioning
confidence: 77%
“…We were somewhat surprised that the impairment in spatial object recognition did not worsen with increasing blast severity, though, and additional studies to explore how this impairment is affected by the direction and complexity of the blast wave is warranted. These additional studies may also resolve past work that shows blast exposure can differentially affect hippocampal-dependent behaviors (Budde et al, 2013; Sajja et al, 2015; Tompkins et al, 2013; Tweedie et al, 2013), a discrepancy that can be explained by characteristics of the blast loading.…”
Section: Discussionmentioning
confidence: 77%
“…To exacerbate the direct injury from blast, there is a gradual acute response of systemic hypoxia on the brain in this polytrauma model. Our group has reported that there are minimal effects on the lungs and therefore an absence of systemic hypoxia after blast-induced mTBI [35, 72]. Future studies will examine oxidative stress and susceptibility of blast-induced BBB breakdown in hypoxic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, learning and memory has been shown to be associated with abnormal levels of myo-inositol, which is an astrogliosis marker (Sajja et al, 2014b ). Resultants of gliosis directed toward dementia, such as tau and DNA methylation markers are found to be upregulated following TBI (Bailey et al, 2015 ; Sajja et al, 2015 ; Shultz et al, 2015 ). Another indicator linked to memory deficits is the disrupted homeostasis of extra and intra-cellular K+ channels in glia (D'Ambrosio et al, 1999 ).…”
Section: Glial Contribution To Memory Deficitsmentioning
confidence: 99%